2010
DOI: 10.1128/jvi.01482-09
|View full text |Cite
|
Sign up to set email alerts
|

Breadth of Human Immunodeficiency Virus-Specific Neutralizing Activity in Sera: Clustering Analysis and Association with Clinical Variables

Abstract: Induction of antibodies that neutralize a broad range of human immunodeficiency virus type 1 (HIV-1) isolates is a major goal of vaccine development. To study natural examples of broad neutralization, we analyzed sera from 103 HIV-1-infected subjects. Among progressor patients, 20% of sera neutralized more than 75% of a panel of 20 diverse viral isolates. Little activity was observed in sera from long-term nonprogressors (elite controllers). Breadth of neutralization was correlated with viral load, but not wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
293
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(334 citation statements)
references
References 36 publications
36
293
5
Order By: Relevance
“…Of note, using a similar technique, Doria-Rose et al reported that plasmablasts were expanded in peripheral blood of HIV ϩ PBMCs and accounted for most of the antigen-specific antibody-secreting cells (ASC) in HIVinfected samples. However, they only found a relationship between development of bNAbs and viral load, and not Env-specific ASC, CD4 ϩ T cell count, or years since diagnosis (2). Thus, the present findings builds upon those of Kardava et al, who reported no significant associations between CD4 T cells (frequency or count) and percent RM Env-specific B cells (17).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Of note, using a similar technique, Doria-Rose et al reported that plasmablasts were expanded in peripheral blood of HIV ϩ PBMCs and accounted for most of the antigen-specific antibody-secreting cells (ASC) in HIVinfected samples. However, they only found a relationship between development of bNAbs and viral load, and not Env-specific ASC, CD4 ϩ T cell count, or years since diagnosis (2). Thus, the present findings builds upon those of Kardava et al, who reported no significant associations between CD4 T cells (frequency or count) and percent RM Env-specific B cells (17).…”
Section: Discussionsupporting
confidence: 81%
“…To study the impact of antigenemia on HIV-specific B cells, we next used a Histagged HIV Env gp120 protein probe study the approximate frequency of gp120-specific B cells between progressors, HIV EC, and HIV VC by flow cytometry, as previously described (2). Healthy donors were assessed as negative controls.…”
Section: Bulk B Cells Are Expanded In Uncontrolled Hiv Infection But mentioning
confidence: 99%
See 1 more Smart Citation
“…Further supporting this point, while X5 was originally considered broadly neutralizing, it has relatively poor neutralizing breadth against various HIV-1 isolates compared to the other antibodies tested here (27) yet demonstrates good breadth as a CAR. Regardless, because BNAbs seem to be escaped by HIV-1 Env variation in their original hosts (28)(29)(30), viral variability and escape may remain a barrier to the therapeutic implementation of BNAb-based CARs.…”
Section: Discussionmentioning
confidence: 99%
“…Breadth of plasma neutralizing activity develops incrementally,48 and evidence suggests that protracted exposure to HIV‐1 Env is required 22, 23, 24, 47, 48, 49, 50. Neutralization breadth is not an all‐or‐nothing phenomenon—in one study, about half of a cohort of 205 chronically infected persons were capable of neutralizing about half of a panel of 219 hard‐to‐neutralize (tier 2) HIV‐1 isolates 45.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%